Verse Rhetoric in the Name of Allah in the Qur'an: An Example of the Perpetrator - Öğretim Üyesi Eid Abdulaziz (Indonesian Journal of Arabic Studies, 2023)
Purpose: This paper aims to examine the word of Allah or Lafz Jalalah as the perpetrator in the Qur’an. On the other hand, this research also deals with Lafzatullah, who is used as the perpetrator, in the context of grammar and language philosophy. Design/ methods/approach: The research uses qualitative methods with the word of Allah or Lafz Jalalah in the Qur’an as the primary focus. The data source used in the study originated from the Qur’an in term of Allah or Lafz. To analyze the word of Allah or Lafz Jalalah in the Qur’an, the author uses a semantic word of Allah, used at two levels as a clear noun and a pronoun. Findings: The semantic approach in this research study confronted with countless facets of eloquence and rhetoric in the name "Allah" in the Quran. From here, we narrowed our focus, concentrating solely on the study of the eloquence of the name "Allah" in the Quran in the context of the active voice. Research implications:  This research contributes to understanding Qur’an from the linguistic studies. contemporary Saudi culture and media. The research proved the accuracy of the systems of the Quran, and the accuracy of its use of the name of the subject, whether it is an apparent name, or an apparent pronoun. And that the Quran is miraculous in its wording, meaning and history. The Prophet was able to challenge the words of the Arabs, who did not leave an attempt to eliminate his call, and try to refute the miracle of the Qur'an. Although they are the ones who owned the corner of the Arabic language, and owned the Arabic rhetoric from all its sides throughout the ages.